Discovery Of Peroxisome Proliferator-Activated Receptor Gamma Agonist - Lee, Guan Sheng (2013)
Peroxisome Proliferator- Activator Receptor gamma (PPARγ) is a nuclear receptor superfamily of ligand activated transcription factor. In biological system, PPARγ plays a crucial role in regulating glucose and lipid metabolism. For that reason, PPARγ has drawn enormous attention as a potential target for designing novel drug to treat type-2- diabetes. PPARγ agonist, Rosiglitazone, is the first line drug for improving insulin sensitivity of type 2 diabetes. However, recent studies indicated that Rosiglitazone are causing undesired side effects like weight gain, oedema and fluid retention. Thus, it is necessary to search for PPARγ agonist for a less complication alternative. In this study, virtual screening using molecular docking approach was done against 5000 compounds; 3000 compounds were from Nature-Based Drug Discovery (NADI®) Database and another 2000 compounds were taken from National Cancer Institute (NCI) Diversity Set 1 library. The top 100 hits with lowest free energy of binding were further analyzed based on their favorable binding mode. A total of four compounds were selected from NCI library and two plants (Temu kunci and Ketumbar) were selected from Malaysia natural resources to test against PPARγ in vitro. From the assay result, the most active compounds from NCI database were NCI37245, which activated PPARγ at EC50 of 43.6nM.While for the selected plants, the methanol crude extracts of Temu kunci was more active compared with Ketumbar. The crude extracts of Temu kunci activate PPARγ at about 1.5 fold higher compared with Ketumbar (1.6 fold) with the EC50 of 50.0ng/mL.